Perubahan Sensitivitas Kaki pada Diabetes Melitus Tipe 2 Setelah Dilakukan Senam Kaki - Laras Sri Ningrum; Tini Wartini; Isnayati Isnayati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The study aimed was to determine the effectiveness of diabetic foot exercises on the sensitivity of the feet of patients with type 2 diabetes mellitus. The method used in this study is a descriptive research method with a case study approach. The results showed that when measuring the feet' sensitivity after doing foot exercises 2x / day for three days, there was a change. Changes in the sensitivity value increased 1-2 points from the maximum point 3. In conclusion, the implementation of foot exercises can improve the feet' sensitivity in patients with type 2 diabetes mellitus. Keywords: Type 2 Diabetes Mellitus, Foot Exercise, Foot Sensitivity